2010
DOI: 10.1021/ml100063w
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Potent, Injectable Inhibitor of Aurora Kinases Based on the Imidazo-[1,2-a]-Pyrazine Core

Abstract: The imidazo-[1,2-a]-pyrazine (1) is a dual inhibitor of Aurora kinases A and B with modest cell potency (IC 50 = 250 nM) and low solubility (5 μM). Lead optimization guided by the binding mode led to the acyclic amino alcohol 12k (SCH 1473759), which is a picomolar inhibitor of Aurora kinases (TdF K d Aur A = 0.02 nM and Aur B = 0.03 nM) with improved cell potency (phos-HH3 inhibition IC 50 = 25 nM) and intrinsic aqueous solubility (11.4 mM). It also demonstrated efficacy and target engagement in human tumor x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…The 19 aurora-A and ligand complex structures with potent activity (IC 50 < 50 nM) were retrieved from the RCSB protein databank. We found that the 19 inhibitors used have a common scaffold in the form of an amine-based aromatic structure which includes quinazolines, imidazopyridines (3MYG [ 9 ]), imidazopyrazines (2X6D [ 10 ]), indazoles, pyrazoles (3FDN [ 3 ]), and substituted pyrimidines (2NP8 [ 11 ]). These amine moieties undergo a crucial H-bonding interaction with the residues around the A213 residue in aurora-A [ 2 ] and serve as criteria for filtering the numerous hits.…”
Section: Resultsmentioning
confidence: 99%
“…The 19 aurora-A and ligand complex structures with potent activity (IC 50 < 50 nM) were retrieved from the RCSB protein databank. We found that the 19 inhibitors used have a common scaffold in the form of an amine-based aromatic structure which includes quinazolines, imidazopyridines (3MYG [ 9 ]), imidazopyrazines (2X6D [ 10 ]), indazoles, pyrazoles (3FDN [ 3 ]), and substituted pyrimidines (2NP8 [ 11 ]). These amine moieties undergo a crucial H-bonding interaction with the residues around the A213 residue in aurora-A [ 2 ] and serve as criteria for filtering the numerous hits.…”
Section: Resultsmentioning
confidence: 99%
“…One explanation for their reticence to react is based on the presence of a basic heteroatom, which has the potential to ligate the palladium center, thus leading to catalyst inhibition or deactivation 2d. 3 Furthermore, despite interest in heterocycles containing a fused imidazole ring, such as imidazo[1,2‐ a ]pyridine,4ac imidazo[1,2‐ b ]pyridazine,4d and imidazo[1,2‐ a ]pyrazine,4e the use of these types of substrates has not been extensively explored in cross‐coupling reactions.…”
Section: Ligand Effects In the Palladium‐catalyzed Amidation Of 4‐bromentioning
confidence: 99%
“…1), with activity against AURKA (IC 50 ≤4 nM) and AURKB (IC 50 ≤13 nM) [15], is currently in preclinical development. While there was one previous pharmacokinetic (PK) study done via IV injection [15], none provide data for oral bioavailability. Further, there is no published bioanalytical assay available to quantitate SCH-1473759.…”
Section: Introductionmentioning
confidence: 99%